2017
DOI: 10.1111/apt.14422
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with network meta‐analysis: first‐ and second‐line pharmacotherapy for moderate‐severe ulcerative colitis

Abstract: Infliximab and vedolizumab are ranked highest as first-line agents, and tofacitinib is ranked highest as second-line agent, for induction of remission and mucosal healing in patients with moderate-severe UC, based on indirect comparisons. Head-to-head trials are warranted to inform clinical decision-making with greater confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
159
1
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(179 citation statements)
references
References 34 publications
6
159
1
13
Order By: Relevance
“…In accordance to our results, a recent systematic review on the burden of ulcerative colitis on functioning suggested that interventions which induce and maintain clinical remission may restore both physical and mental health status, resulting in quality of life comparable to general population . Results are also consistent with evidence on clinical efficacy provided by two recently published network meta‐analyses . Conclusions about the favourable effect of infliximab and vedolizumab on quality of life are in line with previous findings about their efficacy, hence, support their use as first line treatment for induction therapy .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In accordance to our results, a recent systematic review on the burden of ulcerative colitis on functioning suggested that interventions which induce and maintain clinical remission may restore both physical and mental health status, resulting in quality of life comparable to general population . Results are also consistent with evidence on clinical efficacy provided by two recently published network meta‐analyses . Conclusions about the favourable effect of infliximab and vedolizumab on quality of life are in line with previous findings about their efficacy, hence, support their use as first line treatment for induction therapy .…”
Section: Discussionsupporting
confidence: 91%
“…We could not assess small‐study effect in any other outcome due to small number of studies. However, we downgraded confidence in estimates for these outcomes for publication bias by two levels based on evidence for serious under‐reporting of HRQL outcomes in existing trials . In fact, less than 50% of randomised controlled trials for moderate‐to‐severe UC reported data on generic questionnaires, IBDQ response and IBDQ remission, suggesting potential bias of selective reporting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing prestige of the journal is reflected in the most recent increase in our impact factor (IF); during 2019, our 2‐year IF increased from 7.357 to 7.731 ranking AP&T in 11th place among 84 journals in gastroenterology and hepatology. The 10 papers published during 2018 that were the most highly cited during 2019 included such diverse topics as the epidemiology of Helicobacter pylori infection, the intestinal mirobiome and dysbiosis, biologic agents for IBD and evolving treatments for chronic viral hepatitis.…”
mentioning
confidence: 99%